2022
DOI: 10.3390/photonics9120964
|View full text |Cite
|
Sign up to set email alerts
|

Tight Focusing Properties of Ring Pearcey Beams with a Cross Phase

Abstract: We theoretically investigated the properties of tightly focused ring Pearcey beams with a cross phase (CPRPB). The expressions of the distributions of both electric field and magnetic field in the focal region of an objective were first derived from the vectorial Debye theory, and then numerical calculations were carried out to obtain the focused intensity distribution and the Poynting vector of CPRPB near the focus. Numerical calculations indicate that as CPRPB is focused on an objective of high numerical ape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…found that if a non-zero E-field intensity was found in the focus of a circularly polarized optical vortex with phase singularity or a higher-order azimuthally polarized beam with polarization singularity, the energy backflow would occur at the center of the focal plane [5]. Then, further investigation of vector vortex fields passing through a high NA yielded valuable results, enabling the control of the negative energy flow [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…found that if a non-zero E-field intensity was found in the focus of a circularly polarized optical vortex with phase singularity or a higher-order azimuthally polarized beam with polarization singularity, the energy backflow would occur at the center of the focal plane [5]. Then, further investigation of vector vortex fields passing through a high NA yielded valuable results, enabling the control of the negative energy flow [6][7][8].…”
Section: Introductionmentioning
confidence: 99%